MENINGKATKAN PEMAHAMAN KONSEP PESERTA DIDIK TENTANGPENINGGALAN SEJARAH HINDU-BUDHA ISLAM PADA PEMBELAJARAN IPS MELALUI MODEL PEMBELAJARAN MAKE-A MATCH DI SDN KARANG MULYA I - Muhammad Kosambi, Aden (STKIP Subang, 2016)
IPS Learning in school is still not as expected. It can be seen from the lack of understanding the concept of students in social studies learning. Results of the assessment implementation of learning in cycle 1 scored 3.3 with either category, and the second cycle increased with the acquisition value of 3.46 with both categories. While in the third cycle assessment learning implementation to achieve the target indicators of success with the acquisition value of 3.7 with a very good category. The results of the cognitive understanding of the concept of the product (P1) in the first cycle of the data obtained learners who pass as many as 10 0rang learners with a percentage of 43.47%. In the second cycle there was an increase of learners who pass to 15 students with a percentage of 65.21%. In the third cycle increased to reach the indicators of success with learners who completed 20 people learners (86.9%). The result of understanding the concept of cognitive processes (P2) in the first cycle of the data obtained learners who completed a total of 12 0rang learners with a percentage of 52.17%. In the second cycle there was an increase of learners who pass to 16 students with a percentage of 69.56%. In the third cycle increased to reach the indicators of success with learners who completed 20 people learners (86.9%). The result of understanding the concept of psychomotor (P3) in cycle 1 earn a percentage of 60.52%. In the second cycle obtain an increase in the percentage of 78.26%. In the third cycle increased to reach the indicators of success with the acquisition of a percentage of 85.21%.